Effect of Ca/P electrolyte concentration on MAO biofilm on Ti alloy surface. Issue 2 (5th September 2017) - Wang, Fengbiao; Liu, Jingkai; Shu, Qilin
Abstract : In order to prepare functional films containing a predetermined ratio of calcium (Ca) and phosphorus (P) and guide the rational allocation of chemical reagents on a titanium (Ti) alloy surface, calcium/phosphorus biological films were fabricated by using the microarc oxidation (MAO) process. The films' morphology and elemental composition were observed and analyzed. Moreover, a wear resistance test was performed on the film surface. The influence of different concentrations and calcium/phosphorus molar ratios of the films and the MAO system were researched. The effects of electrolyte concentration on the calcium/phosphorus molar ratio of the films were also investigated. The experimental results show that with an increase in electrolyte concentration, the calcium and phosphorus contents of the films all decreased, but the calcium/phosphorus ratio increased. Similarly, the values of the calcium/phosphorus molar ratio and the calcium and phosphorus contents in the films all became lower. Furthermore, a proper electrolyte concentration is helpful in improving the surface properties of the films. If preparation of a film with a certain calcium/phosphorus molar ratio is wanted, this certain ratio can determine the different electrolyte molar concentrations of calcium/phosphorus and it can roughly determine the ratio of the compound reagent and improve the test efficiency.